Zerumbone targets the CXCR4-RhoA and PI3K-mTOR signaling axis to reduce motility and proliferation of oral cancer cells - Zainal, Nur Syafinaz; Gan, Chai Phei; Lau, Beng Fye; Yee, Pei San; Tiong, Kai Hung; Rahman, Zainal Ariff Abdul; Patel, Vyomesh; Cheong, Sok Ching (Elsevier, 2018)
Background: The CXCR4-RhoA and PI3K-mTOR signaling pathways play crucial roles in the dissemination and tumorigenesis of oral squamous cell carcinoma (OSCC). Activation of these pathways have made them promising molecular targets in the treatment of OSCC. Zerumbone, a bioactive monocyclic sesquiterpene isolated from the rhizomes of tropical ginger, Zingiber zerumbet (L.) Roscoe ex Sm. has displayed promising anticancer properties with the ability to modulate multiple molecular targets involved in carcinogenesis. While the anticancer activities of zerumbone have been well explored across different types of cancer, the molecular mechanism of action of zerumbone in OSCC remains largely unknown. Purpose: Here, we investigated whether OSCC cells were sensitive towards zerumbone treatment and further determined the molecular pathways involved in the mechanism of action. Methods: Cytotoxicity, anti-proliferative, anti-migratory and anti-invasive effects of zerumbone were tested on a panel of OSCC cell lines. The mechanism of action of zerumbone was investigated by analysing the effects on the CXCR4-RhoA and PI3K-mTOR pathways by western blotting. Results: Our panel of OSCC cells was broadly sensitive towards zerumbone with IC50 values of less than 5 µM whereas normal keratinocyte cells were less responsive with IC50 values of more than 25 µM. Representative OSCC cells revealed that zerumbone inhibited OSCC proliferation and induced cell cycle arrest and apoptosis. In addition, zerumbone treatment inhibited migration and invasion of OSCC cells, with concurrent suppression of endogenous CXCR4 protein expression in a time and dose-dependent manner. RhoA-pull down assay showed reduction in the expression of RhoA-GTP, suggesting the inactivation of RhoA by zerumbone. In association with this, zerumbone also inhibited the PI3K-mTOR pathway through the inactivation of Akt and S6 proteins. Conclusion: We provide evidence that zerumbone could inhibit the activation of CXCR4-RhoA and PI3K-mTOR signaling pathways leading to the reduced cell viability of OSCC cells. Our results suggest that zerumbone is a promising phytoagent for development of new therapeutics for OSCC treatment.